Dihydrogen phosphate-containing dinuclear double assemblies that demonstrate phosphate reactivity to the tetrafluoroborate anion. Issue 66 (31st July 2018) - Faulkner, Robert A.; Patmore, Nathan J.; Rice, Craig R.; Slater, Christopher
Abstract : LigandsL 1 andL 2 both form dinuclear assemblies with Cu(ii ) and these react with dihydrogen phosphate to give [Cu2 L2 (H2 PO4 )] 3+ . However, in the presence of tetrafluoroborate anions the phosphate undergoes reaction with the anion forming [Cu3 (L 1 )3 (O3 POBF3 )] 3+ and [Cu2 (L 2 )2 (O2 P(OBF3 )2 )] + . Abstract : The ligandsL 1 andL 2 both form dinuclear assemblies with Cu(ii ) and these react with dihydrogen phosphate so that the anion is incorporated within the assembly ( e.g. [Cu2 L2 (H2 PO4 )] 3+ ). However, in the presence of tetrafluoroborate anions the phosphate undergoes reaction with the anion forming [Cu3 (L 1 )3 (O3 POBF3 )] 3+ and [Cu2 (L 2 )2 (O2 P(OBF3 )2 )] + .